THE INFLUENCE OF EXPOSURE TO THE DPR ALLOWANCE ISSUE ON TIKTOK TOWARD PUBLIC TRUST ON DPR’S IMAGE - Muhammad Taufik Hidayat; Haryadi Mujianto; Ridwan Mustopa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Over the past decade, internet penetration in Indonesia has surged, reaching 77% of the total population and positioning digital platforms as essential tools for social interaction and information dissemination. Among these, TikTok has emerged as a significant digital public sphere, particularly regarding political discourse such as the DPR allowance Issue. By applying agenda-setting theory, this study examines the impact of exposure to the DPR allowance issue on TikTok toward public trust on DPR’s Image. Adopting a quantitative approach, data were gathered through questionnaires administered to active TikTok users, selected via purposive sampling. The data were subsequently analyzed using regression analysis via SPSS. The findings indicate that exposure to the DPR allowance issue on TikTok significantly influences public trust on DPR’s image, with statistical results confirming the acceptance of the alternative hypothesis (Ha), where the t-value (9.270) exceeds the critical t-table (1.966). Furthermore, the analysis reveals that this exposure contributes 18.1% to the variance in public trust, suggesting that while the issue is influential, other factors also play a substantial role.